Students’ Perceptions on Teacher’s Oral Feedback - Yustia Septiana; Bukhari Daud; Hendra Heriansyah (Research in English and Education Journal, 2016)
As one of the language skills, speaking is learned in schools both at the level of Junior and senior high school. It is also one of the competencies that must be developed based on the 2013 Curriculum. The curriculum expects the students are able to convey their ideas, opinions, and feeling in daily life contexts. This research was aimed at describing the students’ perceptions toward the use of feedbacks used by the teacher in correcting their oral errors. This study was based on the framework proposed by Calderon (2013). The design of this study was a descriptive qualitative study. To obtain the data, the researcher used a questionnaire. The result of data in this study shows that almost all of the students have positive attitude while there are only very few number of students have negative attitude toward the feedback used by the teacher in an oral activity. Regarding to the result, the researchers suggest the English teachers always correct the students’ errors by giving correction through feedback. It is also suggested for other researchers to conduct further research regarding to what the students’ preferences toward the kinds of feedback used by teacher in correcting students’ oral errors through a deep interview.